Consumer purchasing decision for Halal food at Pasar Tani Mega FAMA / Hamima Hashim - Hashim, Hamima (Faculty of Business and Management, 2010)
This study is mainly about the factors affecting consumer purchasing decision for halal food at Pasar Tani Mega. This study was conducted to measure the factors that affecting consumer purchasing decision for halal food which are halal logo displayed on packaging, awareness of cleanliness, religion of seller and ingredient at Pasar Tani Mega. The purpose of this study is more focusing on to determine the relationship between the factors that affecting consumer purchasing decision for halal food with halal logo displayed on packaging, awareness of cleanliness, religion of seller and ingredient. The respondents for this study are the customers of Pasar Tani Mega. The data from this research was collected by the questionnaire that given to the respondents. Then the data were analyzed using reliability analysis, frequency distribution, cross tabulation, correlation coefficient and multiple linear regressions. Based on the correlations coefficient analysis, it shows that all the four independent variables have significant relationship with the dependent variables which are consumer purchasing decision for halal food at Pasar Tani. Based on the result of multiple linear regressions, it shows that ingredient become the most that affecting the consumer purchasing decision for halal food at Pasar Tani Mega FAMA.